PENGARUH PEMBERIAN KOMPOS AMPAS TAHU TERHADAP PERTUMBUHAN BIBIT KOPI ROBUSTA (Coffea canephora pierre) DI BAWAH NAUNGAN TANAMAN KELAPA SAWIT - Harahap, Ardian Dinarta; Nurhidayah, Tengku; Saputra, Sukemi Indra (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
One of the places that can overshadow the coffee plant seeds is under the shade of oil palm plants. In addition to utilizing shade of oil palm plants, cultivation of coffee in oil palm plantation land is done to make the coffee plants as intercrops. Another factor that consider in coffee plant nursery is fertilization. Fertilization is one way to get a good growth of coffee seeds. This research aims to determine the influence of giving tofu dregs compost and to know better dose for growth of Robusta coffee seeds is under the shade of oil palm plants. This research arrangedÂ  experimentally by using completely randomized design (CRD), which consists of 5 treatment. The treatment was repeated 4 times, so there are 20 experimental units. Each experimental unit contained 2 coffee seeds so that the overall amount of coffee seeds used were 40 seeds, then 1 seeds sampled at each treatment. The observed parameters were the plant height, number of leaves, stem diameter, leaf area and root volume. The results showed that dose of 300 g tofu dregs gives the best results on growth of coffee seeds. Keywords: coffee robusta, compost, tofu dregs